What we've become : living and dying in a country of arms - Metzl, Jonathan, 1964- (W.W. Norton & Company, 2024)
"When a naked, mentally ill white man with an AR-15 killed four young adults of color at a Waffle House, Nashville-based physician and gun policy scholar Dr. Jonathan M. Metzl once again advocated for commonsense gun reform. But as he peeled back evidence surrounding the racially charged mass shooting, a shocking question emerged: Did the public health approach he had championed for years have it all wrong? Long at the forefront of a movement advocating for gun reform as a matter of public health, Metzl has been on constant media call in the aftermath of fatal shootings. But the 2018 Nashville killings led him on a path toward recognizing the limitations of biomedical frameworks for fully diagnosing or treating the impassioned complexities of American gun politics. As he came to understand it, public health is a harder sell in a nation that fundamentally disagrees about what it means to be safe, healthy, or free"--